2021
DOI: 10.1177/03057356211044200
|View full text |Cite
|
Sign up to set email alerts
|

Does music help regulate depressive symptoms for fans of violently themed music?

Abstract: Fans of extreme metal and rap music with violent themes, hereafter termed “violently themed music,” predominantly experience positive emotional and psychosocial outcomes in response to this music. However, negative emotional responses to preferred music are reported to a greater extent by such fans than by fans of non-violently themed music. We investigated negative emotional responses to violently themed music among fans by assessing their experience of depressive symptoms, and whether violently themed music … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For instance, although similar proportions of pop and rock/heavy metal fans report listening to their preferred music when in sad or happy moods, rock/heavy metal fans who felt sadder after listening had higher levels of depression, delinquency, suicidal ideation, and higher rates of self-harm and drug-use (Martin et al, 1993). Relatedly, in a non-clinical sample of 145 young adult fans of heavy metal, rap, or classical music, those who reported a greater magnitude of depressive symptoms were more likely to experience negative emotions (sadness, tension, anger, and fear) in response to their preferred music, and more likely to attempt to regulate depressive symptoms via the discharge mood regulation strategy, rather than diversion (Powell et al, 2021). Notably, both mood regulation strategies did not alleviate (or exacerbate) the experience of negative emotions in those reporting depressive symptoms.…”
Section: Regulating Mood and Emotion With Heavy Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although similar proportions of pop and rock/heavy metal fans report listening to their preferred music when in sad or happy moods, rock/heavy metal fans who felt sadder after listening had higher levels of depression, delinquency, suicidal ideation, and higher rates of self-harm and drug-use (Martin et al, 1993). Relatedly, in a non-clinical sample of 145 young adult fans of heavy metal, rap, or classical music, those who reported a greater magnitude of depressive symptoms were more likely to experience negative emotions (sadness, tension, anger, and fear) in response to their preferred music, and more likely to attempt to regulate depressive symptoms via the discharge mood regulation strategy, rather than diversion (Powell et al, 2021). Notably, both mood regulation strategies did not alleviate (or exacerbate) the experience of negative emotions in those reporting depressive symptoms.…”
Section: Regulating Mood and Emotion With Heavy Metalmentioning
confidence: 99%
“…Another study comparing 145 youngadult fans of heavy metal, rap, or classical music reported no significant differences in depressive symptoms between fan groups. However, the magnitude of depressive symptoms experienced in each fan group was a significant predictor of negative emotional responses to their preferred music (e.g., sadness, tension, anger, and fear) (Powell et al, 2021). There is also some evidence that at least among non-fans, listening to unfamiliar heavy metal (versus rap music) in a single exposure session does not lead to elevated levels of suicidal ideation or anxiety (Ballard & Coates, 1995).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…While sad music has received considerable empirical attention, an emerging body of research on negatively valenced music has focused on the psychosocial risks and benefits of music with violent themes [ 9 ]. Themes of violence in music are primarily found within extreme metal and rap subgenres and are characterised by lyrics that explicitly depict horrific actions of violence that include murder, rape, and body mutilation, often perpetrated by men against women [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the domain of violent visual media more generally, there have been concerns about the negative effects of sustained engagement on psychological well-being; for example, the potential for heightened levels of depression and anxiety, as well as desensitisation to violence coupled with increased aggressive cognitions and behaviours [ 26 , 27 ]. For fans of music with violent themes, there is no conclusive evidence of desensitisation to violence from short or long-term music listening, or evidence that fans have higher levels of depression than fans of non-violently themed music [ 10 , 28 ]. Rather, fans who report positive psychosocial outcomes in response to music containing violent themes may instead experience a ‘spiral up’ of well-being, where frequent engagement with a favourite activity or hobby results in consistent positive emotions and broadened perceptual and attentional capacity, which creates a positive ‘spiral’ that facilitates increased psychological well-being [ 22 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of that fact that the popular media has often vilified particular “problem” genres of music such as metal and rap (Lozon & Bensimon, 2014; Powell et al, 2021), research has demonstrated that the effects of music listening on mental health are contingent upon the individual’s coping style (Horwitz et al, 2018; Renaud et al, 2014) and cognitive awareness (Garrido et al, 2019; Stewart et al, 2019). Music is not always used effectively by people experiencing depression, which is associated with high levels of maladaptive coping (Renaud et al, 2014) including emotion-oriented (Miranda & Claes, 2008) and ruminative coping (Garrido et al, 2019; Stewart et al, 2019) as well as avoidant coping (McFerran & Saarikallio, 2014; White Hughto et al, 2017).…”
mentioning
confidence: 99%